Can a stress management programme reduce stress and improve quality of life in people diagnosed with multiple sclerosis?. Issue 4 (November 2018) - Agland, Susan; Lydon, Amanda; Shaw, Sally; Lea, Rodney; Mortimer-Jones, Sheila; Lechner-Scott, Jeannette
Background: Despite evidence of perceived stress as a risk factor for multiple sclerosis activity, the evidence for managing stress is limited. Objective To evaluate a stress management programme on perceived stress and quality of life, over 6 months. Methods: One hundred people with multiple sclerosis were randomly assigned to either a stress management programme of mindfulness, meditation and progressive muscle relaxation, or wait list. Perceived stress and quality of life were assessed at three intervals across 6 months. Salivary cortisol levels were assessed at two intervals: baseline and first follow-up. Results: The stress management programme did not significantly reduce perceived stress, when comparing mean scores. Secondary analysis using median scores found a significant improvement for quality of life, favouring the intervention group. Conclusion: Stress management had no significant effect on the primary outcome of perceived stress but did improve quality of life in a secondary analysis of median scores.